STRATIGRAPHY, TECTONICSAND MAJOR SEQUENCE BOUNDARY DEVELOPMENT IN TERTIARY SEDIMENTS OF CENTRAL SUMATRA BASIN - Ukat Sukanta; Mac. Endharto (Testing Center for Oil and Gas LEMIGAS, 2005)
According to Satrio and Soejanto (1994), the CPI contract area of Central Sumatra basin has discovered more than 130 fields, and most of these fields are structural traps. The basin is a NW - SE trending elongate depression, which is bounded in the north- west by the Asahan Arc and in the southeast by the Tigapuluh High. To the West, it is bounded by the northwest – southeast trending Barisan Mountains, whereas to the northeast by the Strait of Malacca (Figure 1). The Central Sumatra Basin is based by the Pretertiary basement rocks and has been filled by Eocene up to the Plio-Pleistocene siliciclastic-dominated strata. Based on a three year consulting work for the CPI and discussion with many Earth Scientists of this company, and being supported by much information on the related data from published reports, the senior author has been able to propose scientific contribution on the stratigraphy of the basin and its relationships with tectonism and sea level changes.